2008
DOI: 10.1111/j.1365-2249.2008.03773.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-response to infliximab may be due to innate neutralizing anti-tumour necrosis factor-α antibodies

Abstract: SummaryInfliximab is a chimeric anti-tumour necrosis factor (TNF)-a antibody that is therapeutic in many patients with inflammatory bowel disease. What causes certain patients not to respond is unknown. The question posed is whether innate anti-TNF-a antibodies play any role in the response to infliximab. Blood was drawn prior to the initial dose of infliximab. Serum anti-TNF-a antibodies were quantitated by enzyme-linked immunosorbent assay (ELISA). Affinity-purified anti-TNF-a antibodies were isolated from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Among the 34 infliximab studies, 14 were in IBD and included 2016 patients, 14 were in RA and included 855 patients, 5 were in AS/PsA/psoriasis and included 184 patients and 1 was in a mixed population that included 23 patients with RA and 14 with spondyloarthropathies. However, 1 study in IBD [29] provided no patient numbers and another in the previously mentioned mixed population [47] also included 34 patients with vasculitis; the latter were excluded from the total number of patients provided. Among the 18 adalimumab studies, 3 were in IBD and included 222 patients, 12 were in RA and included 1829 patients and 3 were in AS/PsA/psoriasis and included 86 patients.…”
Section: Search Results and Trial Characteristicsmentioning
confidence: 99%
“…Among the 34 infliximab studies, 14 were in IBD and included 2016 patients, 14 were in RA and included 855 patients, 5 were in AS/PsA/psoriasis and included 184 patients and 1 was in a mixed population that included 23 patients with RA and 14 with spondyloarthropathies. However, 1 study in IBD [29] provided no patient numbers and another in the previously mentioned mixed population [47] also included 34 patients with vasculitis; the latter were excluded from the total number of patients provided. Among the 18 adalimumab studies, 3 were in IBD and included 222 patients, 12 were in RA and included 1829 patients and 3 were in AS/PsA/psoriasis and included 86 patients.…”
Section: Search Results and Trial Characteristicsmentioning
confidence: 99%
“…A study with RA patients showed a frequency of 0% of HACA in patients that received concomitantly infliximab and 7.5 mg/week of MTX versus 7% of these antibodies in patients that were treated only with infliximab [19]. On the other hand, other immunosuppressive drugs, like cyclosporine, azathioprine (AZA), and sulfasalazine, did not have any influence on the development of those antibodies in the RA [24]. In CD, on the other hand, 6-mercaptopurine, AZA, and MTX reduced importantly the incidence of anti-infliximab antibodies [8,[21][22][23]34], but no association was found between the use of mesalamine and the development HACAs [20,21].…”
Section: Anti-infliximab Antibodiesmentioning
confidence: 99%
“…Ebert et al [24] demonstrated the presence of innate anti-TNF-α immunoglobulin G (IgG) antibodies in patients with ulcerative colitis and CD with no influence on clinical response to infliximab. The role of these antibodies has not been clarified and just some of them have neutralizing activity.…”
mentioning
confidence: 99%
“…There is some evidence that antibody formation to infliximab increases the probability of an acute infusion reaction, and reintroduction of the therapy after a long interval is potentially risky (11). To this end, it is evident that acute reactions are not IgE mediated, but generally the underlying mechanisms are poorly understood (12).…”
Section: Introductionmentioning
confidence: 99%